Zeolit Performance in Improving the Quality of Used Oil - Kusumastuti . (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2004)
The aim of this study was to improve the used oil by treatment with zeolite in order to absorb the undesirable components in the oil. Sample of used oil were heated with active zeolite (A1) and natural zeolite (A2) at 2% (B1), 6% (B2) and 10% (B3) in boiled water-bath for 30 minutes. The control was used oil without treatment. After filtered, the oil were analyzed for moisture content, acid number, peroxide value, clearness, colour and viscosity. The results indicated that treating used oil with 10% zeolite could reduce the initial level of tested parameters The reductions were: moisture content and volatile matters 50%, acid number 7% , clearness 3.9% and reduction of peroxide value was 33,8%. However the color and viscosity of the treated oils were not different from the used oil. Active zeolite was more effective than natural zeolite in absorbing the undesirable contaiment. Key words : Zeolite , used oil.